PENCEGAHAN STUNTING DENGAN PEMANFAATAN TANAMAN KELOR BAGI IBU NIFAS - Evicenna Naftuchah Riani; Dewi Ambarwati; Inggar Ratna Kusuma; Diah Atmarina Yuliani (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Children who experience a condition of failure to thrive can be seen by the difference in height where the child is lower than the child's height according to his age or commonly referred to as a stunted child, chronic malnutrition at the beginning of a child's life is the cause. Prevention of stunting in children is attempted on 1,000 HPK (First Day of Life) by giving special attention, one of which is through exclusive breastfeeding. The target for reducing stunting in 2018-2023 is based on the Regional Medium Term Plan (RPJMD) for Banyumas Regency by 15% in 2022. Meanwhile, the target for reducing stunting in Central Java Province for Banyumas Regency in 2022 is 18.1%. The incidence of stunting in Banyumas Regency in children under two years and children under five years is 406 people, pregnant women with a risk of stunting who require referrals are 1749 people and catin (prospective brides) who have a risk of stunting are 84 people. Miraceltree is a plant that has a high nutritional content in Indonesia, often called Moringa leaves with the scientific name Moringa Oleifera. Along with this, WHO indicates that Moringa leaves are an alternative food ingredient as an effort to deal with nutritional problems or malnutrition. The purpose of this research is to explore the benefits of Moringa leaves for postpartum mothers who are breastfeeding so that breast milk production increases so that their nutritional intake is fulfilled as a stunting prevention measure. The qualitative method was chosen in this study with a case study (Case Study). In-depth interviews were used in the study of data on ten postpartum mothers, one village midwife and one coordinating midwife for triangulation in the working area of the Kalibagor Health Center, Banyumas Regency. Lack of information is a factor in the low knowledge about the benefits of Moringa leaves and how to process them. Many general public assume that Moringa leaves are plants that are often found in the home environment and have no benefit in improving nutrition. Several factors influence the utilization of Moringa leaves, namely knowledge or understanding, information, culture, education from health workers (Nakes) and social media.